Empowering the Economy through MSME Adaptation During the Covid-19 Pandemic - Choirunnisa, Luthfi Alif Dinar; Waluyo, Adiet Try; Indrayanti, Wiwin; Nisa, Febriana Khoirun; Ramadhan, Abdul Azis (Indonesian Journal of Social Science Research, 2025)
Micro, small, and medium enterprises (MSMEs) are among the key business sectors that play an important role in the Indonesian economy by meeting daily needs and contributing to overall welfare. MSMEs demonstrated strong resilience during the 1998 monetary crisis, surviving when many larger businesses collapsed, even continuing to grow by absorbing between 85 and 107 million workers by 2012. However, despite this positive performance, MSMEs still encounter varios structural challenges. One of the most significant challenges has been the impact of the COVID-19 pandemic, which has forced MSMEs to adapt new strategies to survive and sustain their development. The purpose of this study is to eximine how MSMEs adaptation strategies contributes to sustaining and stabilizing the economy during the COVID-19 period by analyzing the key inhibiting factors namely human resource limitations, capital constraints, technological challenges, and regulatory barriers that affect their performance. This research employs a literature review (library research) method with a descriptive analytical approach, focusing on MSMEs dynamics during the pandemic, the obstacles they encounter, and the adaptive measures implemented to maintain business continuity and economic resilience